Space stations - Barter, James 1946-; Gale Group (San Diego, Calif. Lucent Books, 2004)
Contains information relating to the launching of a space station, the people who man it, and the countries involved.
Modest beginnings : Salyut and Skylab -- A quantum leap in technology -- Living in outer space -- Space medicine -- Research and experiments -- Have space stations met expectations?
Electronic reproduction.
Keywords: Space stations -- Juvenile literature; Astronautics -- Juvenile literature; Electronic books